Diagnostic Value of Inflammatory Factors in Pathology of Bladder Cancer Patients - Tang, Xingxing; Cao, Yudong; Liu, Jia; Wang, Shuo; Yang, Yong; Du, Peng (Frontiers in Molecular Biosciences, 2020)
Objective: To evaluate the diagnostic value of Inflammatory Factors (IFs) in the pathology of bladder cancer patients. Methods: The patients who were diagnosed with urothelial bladder carcinoma (bladder cancer) and underwent surgical treatment in our center from 2014 to 2019 were enrolled. The values of Neutrophil to Lymphocyte Ratio (NLR), derived Neutrophil to Lymphocyte Ratio (dNLR), Platelet to Lymphocyte Ratio (PLR), Lymphocyte to Monocyte Ratio (LMR), Systemic Immune-inflammation Index (SII) and Prognostic Nutritional Index (PNI) were calculated by blood routine test results before operation. After obtaining the postoperative pathology of the patients, the Area Under Curve (AUC) of Receiver Operating Characteristic (ROC) curves was calculated to evaluate the diagnostic value of these IFs in pathology and their corresponding cut-off values. Results: A total of 641 bladder cancer patients were enrolled. The median values of NLR, dNLR, PLR, LMR, SII and PNI were 6.33, 4.09, 156.47, 2.66, 1114.29 and 51.45, respectively. Grouped patients according to the pathological grade, the NLR, dNLR, PLR and SII of the high-grade group were significantly higher than those of the low-grade group (P<0.001, P<0.001, P<0.001 and P<0.001, respectively), while the LMR and PNI were significantly lower than those of the low-grade group (P=0.003 and P<0.001). Divided patients into non-muscle invasion group (Tis+Ta+T1) and muscle invasion group (T2+T3+T4), in which NLR, dNLR, PLR and SII in the muscle invasion group were significantly higher than those in the non-muscle invasion group (P<0.001, P<0.001, P<0.001 and P<0.001, respectively), while LMR and PNI were significantly lower than those in the low-grade group (P=0.012 and P<0.001). ROC curves analyses showed that NLR, dNLR, PLR, LMR, SII and PNI had predictive value for pathological grade (P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.001, P < 0.001 and P < 0.001, respectively) and muscle invasion (P<0.001, P<0.001, P<0.001, P<0.001, P<0.001, P<0.001 and P<0.001, respectively). Conclusion: The results suggest the higher NLR, dNLR, PLR, SII and lower LMR and PNI are associated with higher risk of high-grade and muscle invasive disease. However, this conclusion needs to be further clarified in the future.